PETscan: measuring incidence of disease phenotypes to prioritize genetic studies in companion animals. (30th July 2018) - Keijser, S. F. A.; Vernooij, J. C. M.; Rothuizen, J.; Fieten, H.; Nielen, M.; Hesselink, J. W.; van Steenbeek, F. G.
Summary: Reliable incidence measurement of diseases is necessary for identification of hereditary diseases in companion animal populations. The data collection system 'PETscan' was developed to facilitate standardized registration of diagnoses in veterinary practice. In the development, we attempted to counter challenges known from other primary practice data systems. PETscan includes a comprehensive list of potential diagnoses and supports the veterinary professionals in the diagnostic process. Demographics, individual data and standardized diagnostic data are collected through practice management software in a central database for epidemiological analysis. A preliminary data analysis from PETscan showed specific health issues in four canine breeds. As a real‐time prospective monitoring tool, PETscan summaries can objectively assess the incidence of disorders in companion animal populations and can be used to prioritize disease–gene identification studies and evaluate the effects of breeding strategies, for example, after implementation of a new DNA test in the breeding strategy.